Pure Mathematics Unit 1 - May 26, 2020

Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

Find cartesian equation

𝑥 = 𝑡2 + 𝑡 + 1 𝑦 = 𝑡2 − 2
𝑡 = √𝑦 + 2

𝑥 = 𝑦 + 2 + √𝑦 + 1 + 1

𝑥 = 𝑦 + 3 + √𝑦 + 1
------------------------------------------------------------------------------------
𝑥 = 3 + 2 cos 𝜃 𝑦 = −5 + 2 sin 𝜃
𝑥−3 𝑦+5
cos 𝜃 = sin 𝜃 =
2 2

2
𝑥−3 2 2
𝑦+5 2
cos 𝜃 = ( ) sin 𝜃 = ( )
2 2
(𝑥 − 3)2 (𝑦 + 5)2
+ = cos2 𝜃 + sin2 𝜃
4 4
(𝑥 − 3)2 + (𝑦 + 5)2 = 4
------------------------------------------------------------------------------------
𝑥 = 3 cos 𝑡 𝑦 = 4 sin2 𝑡
𝑦 = 4(1 − cos2 𝑡)
𝑥 2
𝑥2
cos 𝑡 = cos 𝑡 =
3 9
𝑥2
𝑦 = 4 (1 − )
9
9𝑦 = 36 − 4𝑥 2
4𝑥 2 + 9𝑦 − 36 = 0

------------------------------------------------------------------------------------
𝑥 = 3 sec 𝑡 𝑦 = 2 tan 𝑡
𝑥 𝑦
sec 𝑡 = tan 𝑡 =
3 2
2
𝑥2 2
𝑦2
sec 𝑡 = tan 𝑡 =
9 4
2
𝑥2 2
𝑦2
1 + tan 𝑡 = tan 𝑡 =
9 4
𝑦2 𝑥 2
1+ =
4 9
𝑥 2 𝑦2
− =1
9 4
4𝑥 2 − 9𝑦 2 = 36
------------------------------------------------------------------------------------

𝑥 = 4 + 3 cos 𝑡 𝑦 = −1 + 5 sin 𝑡
𝑥−4 𝑦+1
cos 𝑡 = sin 𝑡 =
3 5
2
(𝑥 − 4)2 2
(𝑦 + 1)2
cos 𝑡 = sin 𝑡 =
9 25
(𝑥 − 4)2 (𝑦 + 1)2
+ = cos2 𝑡 + sin2 𝑡
9 25
(𝑥 − 4)2 (𝑦 + 1)2
+ =1
9 25
------------------------------------------------------------------------------------
𝑥 = cos2 𝑡 − 1 𝑦 = sin 𝑡 − 5
𝑥 = − sin2 𝑡 sin 𝑡 = (𝑦 + 5) → sin2 𝑡 = (𝑦 + 5)2
𝑥 = −(𝑦 + 5)2 →→ 𝑥 + 𝑦 2 + 10𝑦 + 25 = 0

cos 2 𝑡 = (𝑥 + 1) sin2 𝑡 = (𝑦 + 5)2


(𝑥 + 1) + (𝑦 + 5)2 = 1
𝑥 + 𝑦 2 + 10𝑦 + 25 = 0
------------------------------------------------------------------------------------
𝑥 = 5 sec 𝑡 + 2 𝑦 = 4 tan 𝑡 − 3
𝑥−2 𝑦+3
sec 𝑡 = tan 𝑡 =
5 4
2
(𝑥 − 2)2 2
(𝑦 + 3)2
sec 𝑡 = tan 𝑡 =
25 16
2
(𝑥 − 2)2 2
(𝑦 + 3)2
1 + tan 𝑡 = tan 𝑡 =
25 16
(𝑦 + 3)2 (𝑥 − 2)2
1+ =
16 25
(𝑥 − 2)2 (𝑦 + 3)2
− =1
25 16
Find parametric equation
(𝑥 + 1)2 + (𝑦 − 3)2 = 16
(𝑥 + 1)2 + (𝑦 − 3)2 = 16(cos2 𝜃 + sin2 𝜃 )
(𝑥 + 1)2 + (𝑦 − 3)2 = 16 cos2 𝜃 + 16 sin2 𝜃

(𝑥 + 1)2 = 16 cos2 𝜃
𝑥 + 1 = 4 cos 𝜃
𝑥 = −1 + 4 cos 𝜃

(𝑦 − 3)2 = 16 sin2 𝜃
𝑦 − 3 = 4 sin 𝜃
𝑦 = 3 + 4 sin 𝜃

𝑥 = −1 + 4 cos 𝜃 𝑦 = 3 + 4 sin 𝜃
---------------------------------------------------------------------------------

(𝑥 + 3)2 (𝑦 − 5)2
+ =1
25 36
(𝑥 + 3)2 (𝑦 − 5)2
+ = cos2 𝜃 + sin2 𝜃
25 36

(𝑥 + 3)2
= cos2 𝜃
25
𝑥+3
= cos 𝜃
5
𝑥 = 5 cos 𝜃 − 3
(𝑦 − 5)2
= sin2 𝜃
36
𝑦−5
= sin 𝜃
6
𝑦 = 6 sin 𝜃 + 5

𝑥 = 5 cos 𝜃 − 3 𝑦 = 6 sin 𝜃 + 5
------------------------------------------------------------------------------------
(2𝑥 − 1)2 (3𝑦 + 5)2
+ =1
16 49
(2𝑥 − 1)2 (3𝑦 + 5)2
+ = cos2 𝑡 + sin2 𝑡
16 49

(2𝑥 − 1)2
= cos2 𝑡
16
2𝑥 − 1
= cos 𝑡
4
1
𝑥 = 2 cos 𝑡 +
2

(3𝑦 + 5)2
= sin2 𝑡
49
3𝑦 + 5
= sin 𝑡
7
7 5
𝑦 = sin 𝑡 −
3 3
(𝑥 − 8)2 (𝑦 + 1)2
− =1
10 20
(𝑥 − 8)2 (𝑦 + 1)2
− = sec 2 𝑡 − tan2 𝑡
10 20

(𝑥 − 8)2
= sec 2 𝑡
10
𝑥−8
= sec 𝑡
√10
𝑥 = √10 sec 𝑡 + 8

(𝑦 + 1)2
= tan2 𝑡
20
𝑦+1
= tan 𝑡
√20
𝑦 = 2√5 tan 𝑡 − 1
Ends A(1, 4) B(7, 8)
(1 + 7) 4 + 8
𝑀= , = (4,6)
2 2
𝑟 = √(4 − 1)2 + (6 − 4)2 = √13
(𝑥 − 4)2 + (𝑦 − 6)2 = 13

𝑂𝑄 = √42 + 62 = 2√13
𝑂𝐴: 𝑟𝐶2 = √13
𝐶2: 𝑥 2 + 𝑦 2 = 13

𝑂𝐵: 𝑟𝐶3 = 3√13


𝐶3: 𝑥 2 + 𝑦 2 = 117
1
[sin 6𝑥 − sin 2𝑥 ] = (2 cos2 2𝑥 − 1) sin 2𝑥
2
1 1
[sin 6𝑥 − sin 2𝑥 ] = [2 cos 4𝑥 sin 2𝑥 ]
2 2
= cos 4𝑥 sin 2𝑥
= cos 2(2𝑥) sin 2𝑥
We know that cos 2𝑥 = 2 cos2 𝑥 − 1
= (2 cos2 2𝑥 − 1) sin 2𝑥

You might also like